Model Clustering Zona Kesesuaian Lahan menggunakan Kombinasi Algoritma Fuzzy C-Means dan Partition Coefficient Index - Yerymia Alfa Susetyo (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The agricultural sector is one of the vital supporters of national development. The planning of a good agricultural system needs to be supported by looking at the characteristics of each region. The diversity of agricultural areas in Indonesia needs to be simplified by classification according to their similar characteristics. This study aims to group the area of land suitability in an agricultural area. Clustering is obtained using the Fuzzy C-Means algorithm that is validated using the Partition Coefficient Index. Agriculture zone clusters are obtained from the identification of the characteristics of the slope, height, and rainfall of each region. It produced three clusters of land-compatibility zones with almost identical degree of membership. The Partition Coefficient Index algorithm is used to validate the resulting cluster. The results of these three clusters are valid, with PCI membership degrees already grouped according to each cluster. There are two points in the cluster 1, seven points in cluster 2, and eight points on cluster 3.The three clusters that have been generated can facilitate the identification of suitable agricultural land according to their respective characteristics.